2009
DOI: 10.1007/s10620-008-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori Infection on the Expressions of Bax and Bcl-2 in Patients with Chronic Gastritis and Gastric Cancer

Abstract: The aim of the present study is to evaluate the influence of Helicobacter pylori on Bax and Bcl-2 mRNA and protein levels in patients with chronic gastritis and gastric cancer. The study included 217 patients, of which 26 were uninfected; 127 had chronic gastritis and were H. pylori-positive, and 64 had gastric cancer. Bacterial genotypes were evaluated by PCR, and the expression values were determined by quantitative real-time PCR and immunohistochemistry. Our data showed that the up-regulationary effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The consequence of this interaction is the release of proapoptotic Bax that is "peripherally" associated with mitochondria to become integrally associated in the outer mitochondrial membrane leading to cytochrome c release, it binds together with dATP and apoptosis activity factor-1 to procaspase-9, resulting in the activation of downstream caspases that induces proteolytic processing and activation of cell death [47], which explain the current finding of the positive correlation of p53 expression with increase of gastric apoptotic index % in CagA positive patients. This explanation comes in accordance with other studies [19,[48][49][50][51], stated a significant association between HP infection and the expression of Bax which leads to gastric epithelium apoptosis through upregulation of Bax and downregulation of Bcl2. Other stated that HP induces apoptosis in the gastric epithelium through downregulation of the Bcl2 and upregulation of Bax as well as other Bcl2 family proteins such as Bcl-xL and Bak at transcriptional and protein levels under the NF-κB regulations, whether HP express or not the CagA oncoprotein [52].…”
Section: Al-ezzysupporting
confidence: 92%
See 1 more Smart Citation
“…The consequence of this interaction is the release of proapoptotic Bax that is "peripherally" associated with mitochondria to become integrally associated in the outer mitochondrial membrane leading to cytochrome c release, it binds together with dATP and apoptosis activity factor-1 to procaspase-9, resulting in the activation of downstream caspases that induces proteolytic processing and activation of cell death [47], which explain the current finding of the positive correlation of p53 expression with increase of gastric apoptotic index % in CagA positive patients. This explanation comes in accordance with other studies [19,[48][49][50][51], stated a significant association between HP infection and the expression of Bax which leads to gastric epithelium apoptosis through upregulation of Bax and downregulation of Bcl2. Other stated that HP induces apoptosis in the gastric epithelium through downregulation of the Bcl2 and upregulation of Bax as well as other Bcl2 family proteins such as Bcl-xL and Bak at transcriptional and protein levels under the NF-κB regulations, whether HP express or not the CagA oncoprotein [52].…”
Section: Al-ezzysupporting
confidence: 92%
“…Eventually, CagA positive strains cause much more severe lesions at the site of infection by increasing the apoptotic process [53]. The balance between Bax and Bcl2 is known to regulate apoptosis [51]. The apoptotic pathways induced by HP activate Bax, disrupt mitochondrial integrity, and are abrogated by Bcl2 [18].…”
Section: Al-ezzymentioning
confidence: 99%
“…Given that some biological markers, such as oncogenes, tumor-suppressor genes, cell-cycle regulators, and DNA repair genes, were related to tumor genesis, growth, invasion and metastasis, many scientists were dedicated to searching for the new prognostic factors with these molecular markers. Despite of the fact that a few of studies have evaluated the prognostic significance of the markers, such as p53, bcl-2, bax, and c-myc in gastric cancer, the results were controversial [6][7][8][9][10][11]. Moreover, these previous studies were conducted to research the additional prognostic value of the markers to the 6th UICC TNM stage, it was urgent to elucidate the relationship between these makers and the 7th UICC TNM stage.…”
Section: Introductionmentioning
confidence: 99%
“…Homeostasis in the stomach is maintained through a balance between gastric epithelial proliferation and apoptosis (6). However, H. pylori infection affects the normal balance (6)(7)(8)(9)(10)(11). In patients with gastric cancer, there is a disturbance in Bax (the pro-apoptotic protein) and Bcl-2 (the anti-apoptotic protein) balance induced by H. pylori (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, H. pylori infection affects the normal balance (6)(7)(8)(9)(10)(11). In patients with gastric cancer, there is a disturbance in Bax (the pro-apoptotic protein) and Bcl-2 (the anti-apoptotic protein) balance induced by H. pylori (9). Several studies reported that the release of apoptosis-inducing factor from mitochondria is the major pathway involved in H. pyloriinduced apoptosis (10,11).…”
Section: Introductionmentioning
confidence: 99%